Challenges for Non-COVID Patients with Chronic Kidney Disease in Bangladesh: An Observation during Coronavirus Disease Pandemic. (March 2021) - Al Amin, Saif; Morrison, Sharon D.; Kabir, Maheen; Sajib, Md. Refat Uz-Zaman
The coronavirus disease pandemic has created a crisis for patients with chronic kidney disease, as far as getting treatment facilities are concerned. The crisis is more intense in developing countries where the health system is more vulnerable due to poor infrastructures and insufficient health professionals. Bangladesh, being a developing nation, is also facing similar challenges to provide sufficient services to patients with chronic kidney disease. In this short report, we have discussed the challenges and barriers non-COVID chronic kidney disease patients are facing in terms of healthcare access along with getting proper medical interventions and suggested probable strategies to minimize the suffering.